Loss and Dependency: The Story of the Cinderella Complex in Early Adult Women Who Grew Up Without a Father - Rizki Ayu Nurfatima; Rulita Hendriyani (MASI Mandiri Edukasi, 2026)
The absence of a father figure during childhood may influence women’s psychological development in early adulthood, particularly in the emergence of the Cinderella complex. This study aims to describe the manifestation of the Cinderella complex among early adult women who grew up without a father’s presence or role. The research addresses the problem of how fatherlessness contributes to emotional dependence and the need for protection in adult women. This study employed a qualitative descriptive approach using a case study method. The participants consisted of three early adult women aged 18–25 years who experienced fatherlessness due to divorce, death, or psychological abandonment. Data were collected through in-depth interviews, observations, and documentation, and were analyzed using an interactive analysis model. The results indicate that women who grow up without a father tend to seek a substitute for their “first love,” which is often represented by the father figure. This unmet need fosters a dependence on others, particularly men, for protection and emotional security. Participants with Cinderella complex tendencies demonstrated a strong need for physical and emotional closeness, along with difficulties in achieving independence. The findings suggest that the Cinderella complex does not develop solely in women accustomed to receiving assistance but may also emerge in women lacking a father figure, driven by the motivation to find a replacement for the absent protective role. This study highlights the importance of understanding fatherlessness as a contributing factor to the development of emotional dependence in early adult women.